Requirements for the Implementation of Cyber Security in Nizwa University in light of Oman Vision 2040 and its obstacles from the point of view of academics and employees - Al-Balushi, Najla Moosa Mohammed; Al-Rawahi, Teeba Saif Ahmed; Al-Aamri, Badriya Hamood Said; Al-Dhuhli, Rabia AlMur Ali; Al-Yahmadi, Hamed Hilal Hamood; Al-Qudah, Mohammed Ismail Abdullah (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the requirements and obstacles of achieving cybersecurity at the University of Nizwa according to the Oman Vision 2040 from the point of view of academics and the University staff. Descriptive analytical method, survey and questionnaire used as a study tool, applied to a sample of (186) academics and employees. The degree of the requirements came with an average (2.04), with SD (0.58), which is a low score, and all fields came with a low degree, the technical requirements came in the first rank, followed by the cognitive requirements, human resources , and  the logistics requirements.  The degree of obstacles came with an average of (2.67), SD (0.89), which is medium degree, the results also revealed that there are no statistically significant differences at the level of significance (α≤0.05) Among the averages of the estimates of study sample members for the requirements according to the gender variable in all fields, and the total score, while there are significant differences in the field of technical requirements and in favor of males, and the absence of statistically significant differences at (α≤0.05) for the academic grade variable. Based on the results, the researchers recommended continuing to provide the requirements for achieving cybersecurity at the University of Nizwa and training academics and staff to keep up with technological developments and address the development of types of cyber-attacks.
Keywords: Cyber Security; Oman 2040 Vision; University of Nizwa